Peningkatan Keterampilan Gerak Dasar, Tanggung Jawab, dan Tingkat Enjoyment Siswa SD Melalui Model Pembelajaran Teaching Personal and Social Responsibility ( TPSR ) - Mocahamad Krisna Julianto; Dian Budiana; Anira; Lukmannul Haqim Lubay (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aims to increase students' level of enjoyment in taking physical education lessons, to improve elementary school students' basic movement skills through the application of the TPSR learning model, to determine the effect of the TPSR learning model on increasing the personal responsibility of elementary school students in physical education learning. The research uses a quantitative approach with experimental methods. The sampling technique used was total sampling, involving all class IV students at SDN 11 Lembang, totaling 40 students. The research instruments were the Test of Gross Motor Development (TGMD-2) and the TPSR (Teaching Personal and Social Responsibility) questionnaire test, the Physical Activity Enjoyment Scale (PACES) questionnaire test. Data analysis was carried out using descriptive statistics and cross-sectional comparative studies. The results of the Shapiro-Wilk normality test showed that the data was not normally distributed (p < 0.05), so hypothesis testing was carried out using the nonparametric Wilcoxon Signed Rank Test. The results of the Shapiro-Wilk normality test showed that the enjoyment data was not normally distributed (p < 0.05), so the analysis was continued with the nonparametric Wilcoxon Signed Rank Test. The Wilcoxon test results show a value of Z = -5.356b with Asymp. Sig. (2-tailed) = 0.000 < 0.05 for enjoyment. Based on these results, it can be concluded that the application of the TPSR (Teaching Personal and Social Responsibility) learning model in PJOK learning provides a significant increase in the enjoyment and basic movements of elementary school students. These findings indicate that the TPSR model can be an effective teaching strategy for teachers to develop students' movement skills and character in a more balanced manner. Keywords: Basic Movement, Enjoyment, Responsibility, TPSR (Teaching Personal and Social Responsibility)